Temperature dependence of electron properties of Sn doped In2O3 nanobelts - Chiquito, Adenilson J.; Escote, Marcia T.; Orlandi, Marcelo Ornaghi [UNESP]; Lanfredi, Alexandre J. C.; Leite, Edson R.; Longo, Elson [UNESP] (Elsevier B.V., 2007)
This paper reports on the measurements of transport properties of high crystalline quality Sn doped In2O3 nanobelts. The samples presented metallic conduction in a large range of temperatures; however, at low temperatures, the resistivity showed a slight increase and the current-voltage curves showed a tendency to saturate even in the low-voltage range. From these observations, we discuss some arguments on the possibility of low dimensional conducting channels as the main responsible for the conduction at low temperatures. Additionally, we present an alternative technique for production of low resistance ohmic contacts, which can be further used in devices' construction. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: In2O3; nanowires; metallic conduction